Empowerment of Covid Pandemic Women in Reducing Anxiety Using Acuyoga Techniques - Renityas, Nevy Norma; Tinasari, Levi; Agustina, Ika (Journal of Community Service for Health, 2022)
Acuyoga is a combination of acupuncture/acupressure and yoga. Yoga movements accompanied by massage of acupressure points will open the energy blockage pathways that cause several disease complaints, increase children's brain intelligence, and endurance. Acupressure is a part of traditional Chinese medicine, and is widely used in Asia. The benefits of acuyoga are reducing anxiety, insomnia, stress, etc. And research that has been conducted in various countries reports that anxiety disorders cause psychological anomalies during the COVID-19 pandemic. The negative impact of anxiety disorders experienced by individuals is to reduce the body's immunity so that it is susceptible to disease. Anxiety disorders can even make a person commit suicide. If left unchecked, this can become a new problem for public health so it needs special attention. Research related to anxiety disorders of the Indonesian people shows that there are four variables that affect the level of anxiety disorders of the Indonesian people during the pandemic. Namely age, gender, education, and occupation. The metods of the research is total sampling. We put 20 respondens from reproductive woman to know their anxiety, and then we give the acuyoga techniques for resoleve their anxiety, and then we put the result before treatment and after traetment. From the results of the research above the team tried to provide alternative solutions to reduce anxiety in the covid pandemic, namely by doing acuyoga treatment, so in this community service the team tried to do community service "Empowerment of women in the covid pandemic in reducing anxiety in the covid pandemic by using acuyoga techniques".